Anti-Ahmadiyya Rulings in East Sumatra: An Epistemological Review of Religious Opinion in Pre-Independence Indonesia - Ja'far, Ja'far; Umar Muhammad Noor; Asrul, Asrul; Rasyid, Harun Al (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This study examines the religious perspectives on the Ahmadiyya movement in East Sumatra in the early twentieth century. The primary research questions are: What was the official stand of the ‘ulamā’ of the Ahmadiyya movement in East Sumatra? What were the epistemological foundations of their views? To date, there has been no specific research on this topic. Thus, this study aims to provide a historical, sociological, and philosophical review of the rejection of the Ahmadiyya movement that emerged in East Sumatra in the 1930s. This is a library research study employing historical, sociological, and philosophical approaches. Al-Jabiri’s epistemological framework is utilized as a tool to analyze this research topic. The study reveals that the ‘ulamā’ in East Sumatra, particularly Tengkoe Fachroeddin and the Committee for the Eradication of Ahmadiyya Qadiyani Beliefs, concluded that Mirza Ghulam Ahmad and his followers were apostates and infidels. In constructing their knowledge about the Ahmadiyya, they employed rational epistemology. This study argues that the rejection by scholars in East Sumatra is based on rational arguments in reference to the religious sciences they studied. This approach has negative implications as it facilitated the emergence of religious attitudes that are dogmatic, defensive, apologetic, and polemical.